L LITERATURE REVIEW: HUBUNGAN KEPATUHAN KEMOTERAPI DENGAN KUALITAS HIDUP PASIEN KANKER PAYUDARA - Arya Andika Saputra; Rifa'atul Mahmudah; Rina Saputri (LPPM Universitas Sari Mulia, 2021)
Background: Cancer is caused by the growth of abnormal tissue cells. Breast cancer is a major health problem among women. For cancer sufferers must undergo chemotherapy. In the chemotherapy process, you must have a high level of adherence in order to improve your quality of life. Aim: This study was to determine the relationship between chemotherapy adherence and quality of life in breast cancer patients. Methods: this study used a literature review, in which literature searches were sourced from three databases (Pubmed, Doaj, Google Scholer), using keywords according to the theme. Results: Surveillance of breast cancer patients undergoing chemotherapy that was constructed by the stage level and systemic side effects of treatment. The quality of life of breast cancer patients by many factors. The quality of life for breast cancer patients can be improved by providing education. Breast cancer patients who are adherent undergo chemotherapy with good quality of life. Conclusion: There is a relationship who underwent chemotherapy with the quality of life of breast cancer patients. Recommendation: the application of attitudes to breast cancer patients in chemotherapy life can improve the quality of patients.